PEMANFAATAN GLIDEAPPS DALAM PEMBELAJARAN E-LEARNING DI MI MA’ARIF SAMBIROTO TAMAN SIDOARJO - Desi Rahmawati; Nuraini Eka Wahyuning Pratiwi; Aisyah Sukma Nur Rahma Mutmainna; Shinta Pramudya Kusuma Wardani; Julianto Julianto (Universitas Negeri Surabaya, 2021)
In the 21st century, human are facilitated by the sophistication of technology, but it requires skills in the use of technology. It also happens in the world of education which must adapt to current development. Teachers are required to be more creative and innovative to teach their students, where this cannot be separated from the development of effective and flexible learning media. Currently, many learning media use e-learning bases that make it easier for teachers and students, but some of the learning media are considered inefficient. Therefore, this research was conducted to develop a new application-based learning media device from the glideapps to provide a solution for educators at one of the elementary school namely MI Ma'arif Sambiroto in the problem of delivering daily e-learning. This study uses a type of development research method that adapts the ADDIE model (Analyze, Design, Development, Implement, Evaluation). Glideapps allows users to create their own designed applications that can be installed on gadgets, IOS, or laptop, of course this can be used as a learning media that can combine social networking features and learning management systems. The validity of the learning application media in this study was known from the media validation which obtained a percentage of 93.33%, and material validation 86%. The feasibility test is known from the teacher's questionnaire response to get a percentage of 88,7%. Based on the data obtained, it can be concluded that the glideapps application-based learning media is feasible to be used as a learning media.